PENGARUH GELATIN IKAN PATIN (PANGASIUS DJAMBAL) TERHADAP JUMLAH FIBROBLAS PADA LUKA PASCA PENCABUTAN GIGI TIKUS PUTIH (RATTUS NORVEGICUS) - Fredy Mardiyantoro; Fidya Fidya; Dena Savira Andriani (Odonto : Dental Journal, 2019)
Background: Gelatin has been used as a hemostatic agent to stop bleeding and it can be absorbed by human body within 6 hours. The patin fish (Pangasius djambal) gelatin has a high amount of amino acid, especially glutamine which has an important role in increasing the proliferation of fibroblast in wounds. The purpose of this study was to determine the effect of patin fish gelatin to the number of fibroblast in wound after tooth extraction.Method: Rat’s tooth extraction is done on the lower left incisive tooth. Thirty white rats were divided into two groups randomly with 3 time series. Control group was the rats without given of patin fish gelatin and treatment group was the rats given 1cc of patin fish gelatin with pipette. Socket taken for histologically processed by Hematoxylin Eosin staining.Result: It showed there were significant differences in the number of fibroblasts between groups. The Post Hoc Tukey test result showed there was a significant difference between the control group and the treatment group.Conclusion: Patin fish gelatin has effect increasing the number of fibroblast inwound after white rat’s (Rattus norvegicus) tooth extraction